Find:
n → ∞ lim n 1 ∫ 1 ∞ x 2 ln ( 1 + n x ) d x
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
I have a solution without using inequalities.
Hint: 1/x=integral of e^-xy from 0 to inf, dy
My first answer was incorrect because I thought lo g was base 10 and not base e. Perhaps use ln instead of lo g ?
Recall that lim n → ∞ ( 1 + n x ) n = e x . Thus, the natural logarithm of this equality yields lim n → ∞ n ln ( 1 + n x ) = x which, solving for ln ( 1 + n x ) gives lim n → ∞ ln ( 1 + n x ) = n x .
We can now substitute this expression into the given integral and easily solve it.
n → ∞ lim n 1 ∫ 1 ∞ x 2 ln ( 1 + n x ) 1 d x
∫ 1 ∞ n → ∞ lim n 1 x 2 ln ( 1 + n x ) 1 d x
∫ 1 ∞ x 3 1 d x
a → ∞ lim − 2 a 2 1 + 2 1 = 2 1
How are you justifying the interchange of limit and intergration operators?. You would need to prove the uniform convergence of the integral in terms of the parameter n in order to do so. You can use the inequality that @Aman Rajput has used inorder to prove the uniform convergence by Weirestrass M test for integrals.(you'll only need the right hand side of the inequality). Only after that the interchange of limit and integral sign would make sense. Othwerwise your method is very good and quick.
Thanks. I've updated lo g ( ) to ln ( ) .
In the future, if you have concerns about a problem's wording/clarity/etc., you can report the problem. See how here .
Define the sequence of functions f n ( x ) and compute its (point-wise) limit f ( x ) with "l'Hospital's Rule": f n : D : = [ 1 ; ∞ ) → R , f n ( x ) : = n x 2 ln ( 1 + n x ) 1 = x 3 1 ⋅ ln ( 1 + n x ) n x ∣ ∣ ∣ ∣ n → ∞ lim f n ( x ) l’H. = x 3 1 = : f ( x ) Find a dominating function g ( x ) using 1 + h h < ln ( 1 + h ) , h > 0 ( ∗ ) : x > 1 : ∣ f n ( x ) ∣ = f n ( x ) ≤ x 2 1 ⋅ n ln ( 1 + n 1 ) 1 ( ∗ ) < x 2 1 ( 1 + n 1 ) ≤ x 2 2 = : g ( x ) integrable on D Interchange limit and integration using Lebesgue's Dominated Convergence Theorem : n → ∞ lim ∫ 1 ∞ f n ( x ) d x = ∫ 1 ∞ f ( x ) d x = [ 2 x 2 − 1 ] 1 ∞ = 2 1
Problem Loading...
Note Loading...
Set Loading...
Since 1 + y y < lo g ( 1 + y ) < y We can bound the integrand as shown: x 3 1 < n x 2 ln ( 1 + x / n ) 1 < n x 2 ( x / n ) / ( 1 + x / n ) 1 = x 3 1 ( 1 + x / n ) By monotonicity, it satisfies 2 1 = ∫ 1 + ∞ x 3 1 d x < ∫ 1 + ∞ n x 2 ln ( 1 + x / n ) 1 d x < ∫ 1 + ∞ x 3 1 ( 1 + x / n ) d x = 2 1 + n 1 Take the limit and get the answer.